Neurocysticercosis in persons with epilepsy in Medellín, Colombia (1998)
ABSTRACT:Purpose: A prospective series of 643 persons with epilepsy attending a reference neurologic center in Medellin, Colombia, was examined by computed tomography (CT scan) or serology or both with the enzyme-linked immunoelectrotransfer blot assay (EITB) to assess the prevalence of Taenia solium cysticercosis. Methods: All presenting patients were consecutively enrolled in the study. Five hundred forty-six persons underwent cerebral CT scans; 376 of them also had serum EITB performed. Results: Prevalence of neurocys@ercosis by CT scan was13.92%. Overall prevalence of T. solium antibodies with EITB was 9.82%, but for those with late-onset epilepsy (onset afterage 30 years), prevalence increased to 17.5% and 19% for those who originated from outside urban Medellin. Seroprevalence in individuals with mixed lesions (cysts and calcifications) was 88.2% and 64.10% in those with live cysts. Conversely, only 2.72% of persons with CT findings not related to neurocysti- cercosis had positive EITB tests. Conclusions: Our study shows that an important proportion of individuals with epilepsy have radiologic or serologic evidence of T. solium infection, suggesting that neurocysticercosis is an important etiology for epilepsy in Colombia.